Factors Affect Employees Loyalty In Thuy Van Industrial Zone, Phu Tho Province - Vinh, Dr. Luu The; Ly, Bui Thi (The journal of contemporary issues in business and government, 2021)
Employee loyalty, employees’ attitudes, and behaviors play a vital role in the quality of work, at the same time, employees are primarily responsible for guaranteeing competitive advantage and sustainable development for enterprises. To collect data, the research questionnaires were sent to domestic companies in Thuy Van industrial zone. Base on the collected data and by using the method of evaluating the reliability of the scale and the factor analysis. The research analyzed and identified the factors affecting employee loyalty in the companies in Thuy Van industry zone including 4 factors: salary, promotion, relationship, and welfare. In which, the salary was the strongest factor affecting employee loyalty, next was the relationship, advancement opportunities and finally welfare. The research results show that these factors have a positive impact on employee loyalty. Thence, to improve employee loyalty and maintain employees in the company, the research proposed recommendations to so increase employee satisfaction with the above factors will increase their loyalty to the company.